One‐year clinical outcome of biodegradable polymer sirolimus‐eluting stent in diabetic patients: Insight from the ULISSE registry (ULtimaster Italian multicenter all comerS Stent rEgistry). Issue 2 (6th January 2020) - Beneduce, Alessandro; Ferrante, Giuseppe; Ielasi, Alfonso; Pivato, Carlo A.; Chiarito, Mauro; Cappelletti, Alberto; Baldetti, Luca; Magni, Valeria; Prati, Eugenio; Falcone, Stefania; Pierri, Adele; De Martini, Stefano; et al.
Abstract: Background: The ULISSE registry evaluated the real‐world performance of the Ultimaster® biodegradable polymer sirolimus‐eluting stent (BP‐SES) in a multicenter‐independent cohort of patients undergoing percutaneous coronary intervention, including a large proportion of diabetes mellitus (DM) patients. Methods: In this subgroup analysis, 1, 660 consecutive patients, 2, 422 lesions, treated with BP‐SES enrolled in the ULISSE registry were divided in two groups: DM (485 patients, 728 lesions) and non‐DM (1, 175 patients, 1, 694 lesions). Primary endpoint was target lesion failure (TLF), a composite endpoint of cardiac‐death, target‐vessel myocardial infarction (TV‐MI), and clinically driven target lesion revascularization (TLR) at 1‐year. Secondary endpoint was TLR at 1‐year. Results: At 1‐year follow‐up TLF occurred in 5% overall patients and was significantly higher in DM patients (8 vs. 3.7%; p = .001), due to more cardiac deaths (3.4 vs. 1.1%; p = .002). TLR occurred in 3.2% overall patients, and it was not significantly higher in DM compared to non‐DM patients (4.4 vs. 2.8%; p = .114). The incidence of stent thrombosis was low and similar between groups (0.4 vs. 0.9%; p = .526). Insulin‐treated DM (ITDM) patients showed higher rate of TLF as compared to non‐ITDM patients (13 vs. 6.5%; p = .041), but similar rate of TLR (6 vs. 4%; p = .405). After adjustment for relevant comorbidities, DM was not significantly associated with TLF or cardiac death in patients undergoing BP‐SES implantation. Conclusions: This study is the first all‐comers evaluation of BP‐SES in DM patients. Our findings show that DM patients, mostly those with ITDM, still represent a vulnerable population and experience significantly higher rate of TLF. Overall BP‐SES efficacy is considerable, although not statistically significant higher rate of TLR is still present in DM compared to non‐DM patients.